استخدام تقانة زراعة الأنسجة النباتية في الإكثار الدقيق لنبات الرغل الملحي Atriplex halimus L. المتحمل للملوحة والجفاف - زيد سليم (Latakia University Journal -Biological Sciences Series, 2019)
لقد تم التوصل لإيجاد طريقة ناجحة لإكثار نبات الرغل الملحي Atriplex halimus L. في الزجاج, حيث تم استخدام عقل ساقية تحوي برعماً جانبياً واحداً فقط من إحدى شجيرات الرغل التي تنمو في البادية السورية (منطقة الشيخ هلال), وقبل استخدام هذه العقل للزراعة عقمت سطحيا باستخدام هيبوكلوريت الصوديوم أو كلوريد الزئبق, ومن ثم زرعت على وسط Murashige and Skoog (MS) المضاف إليه منظمات نمو مختلفة وبتراكيز مختلفة أيضاً ومنها البنزيل أدنين (BA) أو الكينيتين (Kin) بتركيز 0.5 أو 1.0 mg/L إضافة إلى نفتالين حمض الخل (NAA) وحمض الجبريللين (GA3) بتراكيز 0.1 و 0.2 mg/L على التوالي. وكان أفضل متوسط لتشكل النموات 7.5 برعماً كل أربعة أسابيع على الوسط (1.0 mg/L "BA" + 0.1 mg/L "NAA" + 0.2 mg/L "GA3"). أما التجذير, فقد تشكلت الجذور على النموات خلال 4-2 أسابيع عند زراعتها على وسط (MS) الخالي من منظمات النمو, حيث بلغت نسبة النموات المجذرة 78.5% و نقلت هذه النباتات إلى أصص تحتوي خليطاً من التورب والبرليت بنسبة 1:2, V:V, وتمت تقسيتها خلال 6-5 أسابيع وبنسبة بلغت 65% وبعد ذلك تم نقلها إلى الشروط الطبيعية في الحقل. Successful and detailed in vitro multiplication system for rapid micro- propagation of the forage shrub Atriplex halimus L. has been developed. Nodes with single axillary bud excised from shrubs grown in the field under natural condition at a desert area in AL shikh Hlal were used as primary explants which were surface-disinfected before being placed onto Murashige and Skoog (MS) basal medium containing a combination of growth regulators at different concentration (BA or Kinetin at 0.5 or 1.0 mg/L each with NAA at 0.1 mg/L and GA3 at 0.2 mg/L. Multiplication rate of 7.5 fold was achieved every 4 weeks on Murashige and Skoog (MS) medium supplemented with 1.0 mg/L BA 0.1 mg/L NAA and 0.2 mg/L GA3. These proliferated shoots were sub cultured every 4 weeks for further multiplication. Rooting was achieved during 2-4 weeks on agar-gelled MS basal medium free of growth regulators with 78.5% efficiency rooted plantlets were transplanted into pots with a mixture of 2:1(v/v) Peat: perlite and acclimatized gradually to filed conditions through 5-6 weeks with 65% efficiency and cultivated in the field under natural conditions to evaluate their phenotypic uniformity and field performance.